FAKTOR YANG MEMPENGARUHI KEBIJAKAN DALAM PEMBERIAN KREDIT PADA PERBANKAN UMUM KONVENSIONAL - Fangky A Sorongan (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2019)
Banks are one of the important sectors for the economy in Indonesia. The biggest risk in banks comes from the provision of credit, therefore banks must conduct credit risk analysis and still prioritize the principle of prudence in channeling credit. This research was conducted with the aim to find out what factors could influence policy in lending. The type of research used is quantitative research using secondary data. The results of this study indicate that Third Party Funds (DPK) have a significant positive effect on lending to commercial banks in Indonesia. Capital Adequacy Ratio (CAR) has no effect on lending to commercial banks in Indonesia. Non Performing Loans (NPL) have a significant negative effect on lending to commercial banks in Indonesia. The IDR / USD exchange rate has no effect on lending to commercial banks in Indonesia. The BI Rate has no effect on lending to commercial banks in Indonesia.